Investigate how frequently dental professionals conduct oral cancer screenings during routine dental check-ups and the methods they use - Sindhu Sudhakar Kumararama; Sejal Patel; Nirav Hemant Parekh; Purvi Bhate; Bhavna Jha Kukreja; Trina Hazra; Amit Kumar; Bhumika Kamal Badiyani (Wolters Kluwer Medknow Publications, 2024)
Background: Oral cancer is a significant global health concern with substantial morbidity and mortality rates. Early detection during routine dental check-ups is crucial for improved patient outcomes. Dental professionals play a pivotal role in conducting oral cancer screenings, but the frequency and methods they employ remain understudied. Aim: This cross-sectional study aimed to investigate the frequency of oral cancer screenings during routine dental check-ups conducted by dental professionals and the methods they commonly use. Materials and Methods: A survey was administered to 500 dental professionals, including dentists and dental hygienists, representing diverse demographics and practice settings. The survey collected data on the frequency of oral cancer screenings and the primary methods employed. Descriptive statistics and Chi-square tests were used for data analysis. Results: The study found that 85% of dental professionals conduct oral cancer screenings during routine dental check-ups, with 48% performing them annually and 33% at every visit. Visual inspection (97%) and palpation (83%) were the most commonly used methods, while adjunctive screening tools (45%) were less frequently incorporated. Conclusion: Dental professionals are actively engaged in oral cancer screenings during routine dental check-ups, demonstrating a commitment to early detection. Visual inspection and palpation are commonly employed methods, but there is room for improvement in the adoption of adjunctive screening tools.